طرائق التشخيص والتدبير الجراحي لكيسات الكبد المائية - حاج قاسم, فؤاد; مسعود, سجيع; شحود, قصي (Latakia University Journal -Medical Sciences Series, 2019)
شملت لدراسة 38 حالة كيسة مائية في الكبد، تمت دراستهم ومعالجتهم جراحياً في قسم الجراحة بمشفى الأسد الجامعي باللاذقية في الفترة ما بين 1998-2003. كان المرض أكثر شيوعاً عند الإناث 63.15%، قمة الحدوث في العقدين الرابع والخامس. كان الفص الأيمن أكثر إصابة بنسبة 57.89%. كشف المرض صدفة في 21% من لحالات، بينما كان حس الثقل وعدم الارتياح في المراق الأيمن أكثر الأعراض حدوثاً بنسبة 76.3%. أما العلامة الأكثر مصادفة فكانت الإيلام في المراق الأيمن بنسبة 50%. بدراسة الاستقصاءات المخبرية وجدنا أن الحمضات كانت مرتفعة في 31.57% من الحالات. أما اختبار التراص الدموي غير المباشر فكان إيجابياً في 78.57% من الحالات. أما بالنسبة للاستقصاءات الشعاعية فقد أظهرت الصورة البسيطة للبطن وجود الكيسة في 7.89% من الحالات، بينما بلغت دقة الإيكو 89.47% والتصوير المقطعي المحوسب 100%. خضع جميع مرضى الدراسة للجراحة بعد التشخيص الصحيح حيث تم تحضيرهم بمركبات الهيدروكورتيزون وريدياً قبل الجراحة. كان الشق تحت الأضلاع اليمنى أكثر استخداماً في 37 حالة بنسبة 97.36%. أكثر الطرق الجراحية استخداماً كان تفريغ الكيسة وتدبير الجوف المتبقي بنسبة 92.1%. تم استخدام المحلول الملحي المركز لقتل الطفيلي في جميع الحالات. أما بالنسبة للجوف المتبقي فقد تم تدبيره بوضع مفجِّر في 68.57% من الحالات. كان انصباب الجنب أكثر المضاعفات شيوعاً 47.36%، الناسور الصفراوي في 13.15%، خمج الجرح 7.89%، وحدثت الوفاة في حالة واحدة 2.63%. This study includes 38 cases of hypatic hydrated cysts, which have been studied and managed surgically in the department of surgery in AL-Assad hospital – Lattakia between 1998-2003. The disease was more common in females 63.15%, and the top of incidence was in the fourth and fifth decades. The most common location of disease was in right lope 57.89%. The disease was diagnosed by coincidence in 21% of the cases, while discharge feeling uncomforted in the upper right quadrant was the major symptom 76.3%. The major sign was tenderness in the upper right quadrant in 50%. By analyzing laboratory investigations we found that eosinophyles was raised in 31.57% of the cases. Undirect blood agglutination was positive in 78.57% of case. By studying radiological investigations, the abdominal X-ray showed the cyst in 7.89% of the cases, while the accuracy of ultra sound waves was 89.47%, and the accuracy of C.T was 100%. All patients had surgery after exact diagnosis, they were prepared by hydrocortisone compounds (I.V) before surgery. The right sup-costal incision was used in most cases in 37 cases (97.36%). The best surgical ways was leakage of the cyst and management of of the remain cavity in 92.1%. Concentrated salt solution was used in most cases for killing the parasite. The remain cavity was managed by using a drain in 68.57%. Hydro thorax was the most common complication in 47.36%, bile fistula in 13.15%, wound infection in 7.89% and death occurred in one case (2.63%).